Bimbingan teknis penyusunan laporan keuangan umkm di Kabupaten Rokan Hilir - Desmiyawati Desmiyawati; Susilatri Susilatri; Hari Ardiansyah (Unri Conference Series: Community Engagement, 2020)
So far, the potential of MSMEs has not been fully exploited. Many MSME activity actors (owners) often experience internal problems so that it is difficult to develop and compete both among MSMEs and with large producers. The problem of financial management is one of the problems that is often encountered in MSMEs. Some of the common financial management problems that are often encountered in MSMEs include the mixing of owner's personal finances with business finance, product pricing is often done simply and intuitively, without carefully calculating costs incurred, the method of recording transactions carried out is still not good and lack of knowledge about financial recording and financial management (accounting). Based on these problems, community service activities were carried out in collaboration between the service team, the Rokan Hilir Regency Cooperatives and UKM Service and several MSME players in Rokan Hilir Regency. The purpose of this activity is to increase the willingness or desire of MSME actors in Rokan Hilir Regency to use accounting to improve the financial performance of MSMEs. Then with this activity, it is hoped that participants will be able and skilled to prepare financial reports according to SAK EMKM so that it is useful in improving the performance of MSMEs.The results of the activity provide additional knowledge and understanding to MSME actors how the process of preparing financial statement is in accordance with SAK EMKM. Participants who are MSME players can compile financial statement starting with journalizing, posting to ledgers, trial balance and preparing income statements and statements of financial position